IMPLEMENTASI TEKNOLOGI FILTRASI AIR DALAM PENYEDIAAN AIR BERSIH PASCABANJIR DI MEUNASAH TUHA KECAMATAN MANYAK PAYED KABUPATEN ACEH TAMIANG - Muhammad Syahril; Syamsul Bahri Widodo; Zainal Arif; Taufan Arif Adlie; Muhammad Amin; Suheri (Fakultas Teknik, Universitas Samudra, 2026)
This community service activity aimed to improve the quality of post-flood well water through the implementation of a filtration system and to provide a more adequate clean water supply facility for the community at Salman Alfarisy Mosque, Ie Bintah Village, Manyak Payed District, Aceh Tamiang Regency. The implementation method consisted of field surveys and problem identification, system design, fabrication and preparation of components, installation of the filtration and water distribution systems, and operational testing of the system. The constructed system comprised a water pump, a multi-stage filtration unit utilizing gravel, silica sand, and activated carbon as filter media, storage tanks, distribution tanks, and a piping network connected to the ablution facilities. The results demonstrated that the implemented system operated effectively and produced clearer water compared to the condition prior to filtration. In addition to improving the physical quality of water, the system also supported the sustainable availability of clean water for ablution and other community activities within the mosque environment. The activity further enhanced community understanding of the operation and maintenance of the installed system. Therefore, the implementation of the filtration system can serve as an effective and sustainable solution for providing clean water in flood-affected areas.